2020
DOI: 10.1093/mnras/staa3759
|View full text |Cite
|
Sign up to set email alerts
|

Most of the cool CGM of star-forming galaxies is not produced by supernova feedback

Abstract: The characterization of the large amount of gas residing in the galaxy halos, the so called circumgalactic medium (CGM), is crucial to understand galaxy evolution across cosmic time. We focus here on the the cool (T ∼ 104 K) phase of this medium around star-forming galaxies in the local universe, whose properties and dynamics are poorly understood. We developed semi-analytical parametric models to describe the cool CGM as an outflow of gas clouds from the central galaxy, as a result of supernova explosions in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 110 publications
(188 reference statements)
0
23
0
Order By: Relevance
“…Using the example of the latter, assuming a cooling wind -either due to adiabatic expansion (Wang 1995;Thompson et al 2016) or via mixing induced cooling (Armillotta et al 2017;Gronke & Oh 2020a), one can obtain cold gas material transported into the CGM with mass of order the stellar mass of the galaxy. It has been argued, however, that the assumed mass loading factors of the wind need to be rather large and / or the observed cold gas velocities are too small (Bouché et al 2012;Afruni et al 2020). Furthermore, in reality galactic winds are not purely radial but also possess some turbulent components that might destroy the cold gas embedded in galactic winds (Vijayan et al 2020;Schneider et al 2020) -an effect that is usually ignored in 'cloud crushing' studies such as ours (Gronke & Oh 2018, 2020a.…”
Section: Implications For the Origin And Survival Of Cold Gas In The Cgmmentioning
confidence: 92%
“…Using the example of the latter, assuming a cooling wind -either due to adiabatic expansion (Wang 1995;Thompson et al 2016) or via mixing induced cooling (Armillotta et al 2017;Gronke & Oh 2020a), one can obtain cold gas material transported into the CGM with mass of order the stellar mass of the galaxy. It has been argued, however, that the assumed mass loading factors of the wind need to be rather large and / or the observed cold gas velocities are too small (Bouché et al 2012;Afruni et al 2020). Furthermore, in reality galactic winds are not purely radial but also possess some turbulent components that might destroy the cold gas embedded in galactic winds (Vijayan et al 2020;Schneider et al 2020) -an effect that is usually ignored in 'cloud crushing' studies such as ours (Gronke & Oh 2018, 2020a.…”
Section: Implications For the Origin And Survival Of Cold Gas In The Cgmmentioning
confidence: 92%
“…What our results show is that, contrary to down the barrel inferences and what is commonly assumed, MgII in emission is a good probe of gas inflowing through the inner CGM. The ultimate balance of inflow versus outflow in the origin of cool gas in the CGM remains an open theoretical question (Voit 2021;Afruni et al 2021).…”
Section: Mgii Emission In Outflowsmentioning
confidence: 99%
“…Even for field galaxies, cold gas traced by HI 21cm line emission is extremely rare beyond 20-35 kpc (Borthakur 2016;Borthakur et al 2014), whereas Lyα tracing warm partially neutral gas is ubiquitous within the virial radius. Recent semi-analytical modeling by Afruni et al (2021) has also shown that star formation-driven outflows may not be the primary source of the cool CGM traced by Lyα and other low-ionization metal lines. Therefore, we can conclude safely that AHCs are not likely to reach much further from the disk and would either return to the disk or get assimilated into the hot inner CGM.…”
Section: The Fate Of Ahcs and Their Connection To The Cgmmentioning
confidence: 99%